An antistatic PP composite material based on high gloss carbon black and preparation method thereof
The high-gloss carbon black after surface modification is blended with polypropylene material to form an anti-static PP composite material, which solves the problem of poor anti-static performance of polypropylene material and achieves a combination of high gloss and good anti-static properties.
Patent Information
- Application Number
- CN202411854907.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-17
AI Technical Summary
Simple polypropylene materials have poor anti-static properties and are prone to electrostatic accumulation in specific environments, limiting their application range in certain electrostatic sensitive applications, especially in finishing materials.
High gloss carbon black is used as a conductive filler, and the gloss and conductive properties of carbon black are improved through surface modification treatment, and blended with polypropylene material to form an antistatic PP composite material.
The good antistatic properties and high gloss of polypropylene materials have been achieved, and the application prospects of them have been expanded in fields with high decorative and gloss requirements.
Smart Images

Figure CN119307044B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polypropylene composites, and in particular relates to an antistatic PP composite material based on high-gloss carbon black and a preparation method thereof. Background Art
[0002] As an important thermoplastic, polypropylene (PP) material has been widely used in various industries due to its excellent chemical stability and cost-effectiveness. In the field of composite materials and decoration, polypropylene is particularly favored due to its light weight, dimensional stability and chemical corrosion resistance.
[0003] However, pure polypropylene material has poor antistatic properties and is prone to static electricity accumulation under certain circumstances, which limits its application in certain static-sensitive applications, especially in finishing materials, where static electricity can easily absorb dust in the air, resulting in insufficient aesthetics of the finish.
[0004] In order to overcome the above problems, various methods including adding conductive fillers are used in the prior art to reduce the electrostatic properties of polypropylene materials. Among them, carbon black, as an ideal conductive filler, has a significant effect in long-term antistatic performance due to its extremely high conductivity and low cost. However, carbon black particles have a complex porous structure and a surface area with many defects, which not only enables them to effectively absorb or scatter light, but also causes the glossiness of the surface of the polypropylene material to decrease, causing the polypropylene products to lose transparency and smooth appearance, which significantly limits its application in fields with high requirements for decorativeness and gloss. Summary of the invention
[0005] In order to solve the technical problems mentioned in the background technology, the object of the present invention is to provide an antistatic PP composite material based on high gloss carbon black and a preparation method thereof.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] An antistatic PP composite material based on high-gloss carbon black comprises the following raw materials in parts by weight: 100 parts of PP resin, 15-20 parts of POE resin, 8.5-12 parts of high-gloss carbon black, 0.6-0.8 parts of antistatic additive, 10-15 parts of filler, 2.5-3.5 parts of lubricant and 0.12-0.15 parts of antioxidant.
[0008] The high gloss carbon black is prepared by the following method:
[0009] Step A1: Preheat pentaerythritol tetraacrylate, p-hydroxythiophenol and ethyl acetate to dissolve, introduce nitrogen protection, then add photoinitiator and mix well, then control the temperature to 55-70°C, use 150-220W / m 2UV irradiation, stirring at 90-120 rpm for 2.5-3.5 hours, removing ethyl acetate after the reaction is completed to obtain a surface modifier;
[0010] Furthermore, the feed ratio of pentaerythritol tetraacrylate, p-hydroxythiophenol, photoinitiator and ethyl acetate is 10mmol:40mmol:6-10mg:80-110mL. Under ultraviolet initiation, the active thiophenol structure of p-hydroxythiophenol and the terminal double bond of pentaerythritol tetraacrylate are click-added to introduce terminal phenol structure modification. The specific reaction process can be expressed as follows:
[0011]
[0012] Step A2: Mix the surface modifier and acetone at a high temperature, add the conductive carbon black and disperse them by ultrasonic, then let the dispersion stand for 24 hours, take the bottom precipitate and wash it with ethanol, centrifuge it again and vacuum dry it to constant weight to obtain modified carbon black;
[0013] Furthermore, the feed ratio of the conductive carbon black, the surface modifier and the acetone is 50g:3.2-4.4g:270-350mL, the molecular weight of the surface modifier is relatively high, and the molecule contains a large number of benzene ring structures, and the porous structure on the surface of the conductive carbon black has a strong adsorption effect, and the surface modifier is adsorbed and loaded onto the surface pore wall of the conductive carbon black to form a composite modification;
[0014] Preferably, the average particle size of the conductive carbon black is 30-50 nm. Within this particle size range, the carbon black is easily dispersed and colored and forms a continuous conductive network. At the same time, it has good adsorption properties and can effectively load the surface modifier in the gaps.
[0015] Step A3: The modified carbon black, aniline and tetrahydrofuran are stirred and dispersed, and then hydrochloric acid is added and mixed. The temperature of the water bath is controlled at 40-60° C., and ammonium persulfate solution is slowly added to react for 3.5-5.5 hours. After the reaction is completed, the precipitate is centrifuged and washed with water until neutral and dried to obtain high gloss carbon black;
[0016] Furthermore, the feed ratio of modified carbon black, aniline, ammonium persulfate, hydrochloric acid and tetrahydrofuran is 50g:7.8-9.5g:1.2-1.8g:300-400mL:70-90mL. The surface modifier molecules adsorbed on the surface of the modified carbon black contain a large number of ester groups and phenolic hydroxyl groups, which produce hydrogen bonds with aniline, enriching aniline in the surface voids of the modified carbon black, and the phenolic hydroxyl groups provide protons to protonate the aniline molecules in the voids, preferentially starting the polymerization process, and forming polyaniline filling in the carbon black voids.
[0017] Preferably, the antistatic auxiliary agent is selected from anionic antistatic agents to synergistically reduce the surface resistance of the composite material.
[0018] Preferably, the filler is compounded from talcum powder and glass fiber powder.
[0019] A method for preparing an antistatic PP composite material based on high-gloss carbon black, specifically comprising: premixing high-gloss carbon black, an antistatic additive and a filler, then melt-blending PP resin, POE resin, a lubricant and an antioxidant at 180-190° C., then adding the premix, continuing to heat to 210° C. and kneading until the torque is stable, discharging and cooling, and obtaining a PP composite material.
[0020] Beneficial effects of the present invention:
[0021] The invention is based on a carbon black composite PP antistatic material, and the surface of traditional carbon black is modified to prepare high-gloss carbon black. After being blended with a PP material, the composite material is endowed with good antistatic performance and high gloss, and has broad application prospects in high-gloss antistatic finishing materials; the high-gloss carbon black is prepared by click addition of p-hydroxythiophenol and pentaerythritol tetraacrylate under light initiation, and a phenol structure is introduced into the molecular end of pentaerythritol tetraacrylate to obtain a surface modifier, the molecule of the surface modifier is relatively high, and a large number of benzene ring structures are contained in the molecule, which are adsorbed by the carbon black into the surface pores to form a composite modification, and in the process of liquid-phase chemical oxidation of polyaniline, the ester group and the phenolic hydroxyl group in the surface modifier molecule generate hydrogen bonds with aniline The aniline is enriched in the surface voids of the modified carbon black, and the phenolic hydroxyl group provides protons to protonate the aniline molecules in the voids, preferentially start the polymerization process, and form polyaniline filling in the carbon black voids; compared with common carbon black materials, the high-gloss carbon black of the present invention has a smooth surface, which reduces the scattering and absorption of light between carbon black particles, and more light can directly pass through the plastic or be reflected on its surface instead of being scattered in all directions, thereby making the composite material have a higher glossiness. In addition, carbon black is used as a dispersed phase in the composite material, and its smooth surface makes it easier to disperse evenly in the material. In addition, the surface-filled polyaniline has good conductivity and is easy to form a large number of conductive networks, which significantly improves the antistatic property of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0023] Figure 1 This is an electron microscope image of the high gloss carbon black prepared in Example 4 of the present invention. DETAILED DESCRIPTION
[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Example 1, preparation of an antistatic PP composite material based on high gloss carbon black, the specific implementation process is as follows:
[0026] (1) Preparation of high gloss carbon black
[0027] Step A1: Preheat pentaerythritol tetraacrylate, p-hydroxythiophenol and ethyl acetate to 40°C for mixing, introduce nitrogen for protection, then add photoinitiator and mix well, then control the temperature to 70°C, use 150W / m 2 UV irradiation was applied and stirred at 120 rpm for 2.5 hours, wherein the feed ratio of pentaerythritol tetraacrylate, p-hydroxythiophenol, photoinitiator and ethyl acetate was 10 mmol: 40 mmol: 6 mg: 110 mL, and the photoinitiator was selected from photoinitiator 1173. After the reaction, ethyl acetate was removed by rotary evaporation to obtain a surface modifier.
[0028] Step A2: The surface modifier and acetone are heated to 50°C for mixing, conductive carbon black is added for ultrasonic dispersion, and the dispersion is allowed to stand for 24 hours, wherein the feed ratio of conductive carbon black, surface modifier and acetone is 50g:3.2g:270mL, and the conductive carbon black is selected from LI-400 type raw material with an average particle size of 48nm. Then, the bottom precipitate is washed with ethanol, and the precipitate is centrifuged again and vacuum dried to constant weight to obtain modified carbon black.
[0029] Step A3: Stir and disperse the modified carbon black, aniline and tetrahydrofuran, then add hydrochloric acid to mix, control the temperature of the water bath to 60°C, apply 90rpm stirring and slowly add ammonium persulfate solution to react for 3.5h, wherein the feed ratio of modified carbon black, aniline, ammonium persulfate, hydrochloric acid and tetrahydrofuran is 50g:7.8g:1.2g:300mL:70mL, the ammonium persulfate solution is a saturated aqueous solution at room temperature, and the concentration of hydrochloric acid is 1mol / L. After the reaction is completed, centrifuge and take the precipitate, wash with water to neutrality, and dry to obtain high gloss carbon black.
[0030] (2) Preparation of PP composite materials
[0031] Ingredients: The raw materials are calculated by weight: 100 parts of PP resin, K1008 type resin raw material is selected; 20 parts of POE resin, LC670 type resin raw material is selected; 12 parts of high gloss carbon black, which is self-made in this embodiment; 0.8 parts of antistatic additive, selected from sodium dodecylbenzene sulfonate; 10 parts of filler, selected from talcum powder and glass fiber powder, compounded in a weight ratio of 2:1; 3.5 parts of lubricant, selected from calcium stearate; 0.12 parts of antioxidant, selected from antioxidant 1010 and antioxidant 168, compounded in a weight ratio of 1:1.
[0032] Blending: Premix high gloss carbon black, antistatic additive and filler, then melt blend PP resin, POE resin, lubricant and antioxidant at 180°C, then add the premix, continue to heat to 210°C and knead until the torque is stable, cool the material out, and obtain a PP composite material.
[0033] Example 2, preparation of an antistatic PP composite material based on high gloss carbon black, the specific implementation process is as follows:
[0034] (1) Preparation of high gloss carbon black
[0035] Step A1: Preheat pentaerythritol tetraacrylate, p-hydroxythiophenol and ethyl acetate to 40°C for mixing, introduce nitrogen for protection, then add photoinitiator and mix well, then control the temperature to 55°C, use 220W / m 2 Ultraviolet irradiation was applied and stirred at 90 rpm for 3.5 hours, wherein the feed ratio of pentaerythritol tetraacrylate, p-hydroxythiophenol, photoinitiator and ethyl acetate was 10 mmol: 40 mmol: 10 mg: 80 mL, and the photoinitiator was selected from photoinitiator 1173. After the reaction, ethyl acetate was removed by rotary evaporation to obtain a surface modifier.
[0036] Step A2: The surface modifier and acetone are heated to 50°C for mixing, conductive carbon black is added for ultrasonic dispersion, and the dispersion is allowed to stand for 24 hours, wherein the feed ratio of conductive carbon black, surface modifier and acetone is 50g:4.4g:350mL, and the conductive carbon black is selected from VULCAN XC-72 raw material with an average particle size of 30nm. Then, the bottom precipitate is washed with ethanol, and the precipitate is centrifuged again and vacuum dried to constant weight to obtain modified carbon black.
[0037] Step A3: Stir and disperse the modified carbon black, aniline and tetrahydrofuran, then add hydrochloric acid to mix, control the temperature of the water bath to 40°C, apply 60rpm stirring and slowly add ammonium persulfate solution to react for 5.5h, wherein the feed ratio of modified carbon black, aniline, ammonium persulfate, hydrochloric acid and tetrahydrofuran is 50g:9.5g:1.8g:400mL:90mL, the ammonium persulfate solution is a saturated aqueous solution at room temperature, and the concentration of hydrochloric acid is 1mol / L. After the reaction is completed, centrifuge and take the precipitate, wash with water to neutrality, and dry to obtain high gloss carbon black.
[0038] (2) Preparation of PP composite materials
[0039] Ingredients: The raw materials are calculated by weight: 100 parts of PP resin, K1008 type resin raw material is selected; 15 parts of POE resin, LC670 type resin raw material is selected; 8.5 parts of high gloss carbon black, which is self-made in this embodiment; 0.6 parts of antistatic additive, selected from sodium dodecylbenzene sulfonate; 15 parts of filler, selected from talcum powder and glass fiber powder, compounded in a weight ratio of 2:1; 2.5 parts of lubricant, selected from calcium stearate; 0.15 parts of antioxidant, selected from antioxidant 1010 and antioxidant 168, compounded in a weight ratio of 1:1.
[0040] Blending: Premix high gloss carbon black, antistatic additive and filler, then melt blend PP resin, POE resin, lubricant and antioxidant at 190°C, then add the premix, continue to heat to 210°C and knead until the torque is stable, cool the material out, and obtain a PP composite material.
[0041] Example 3, preparation of an antistatic PP composite material based on high gloss carbon black, the specific implementation process is as follows:
[0042] (1) Preparation of high gloss carbon black
[0043] Step A1: Preheat pentaerythritol tetraacrylate, p-hydroxythiophenol and ethyl acetate to 40°C for mixing, introduce nitrogen for protection, then add photoinitiator and mix well, then control the temperature to 60°C, use 180W / m 2 UV irradiation was applied and stirred at 120 rpm for 3.2 hours, wherein the feed ratio of pentaerythritol tetraacrylate, p-hydroxybenzenethiol, photoinitiator and ethyl acetate was 10 mmol: 40 mmol: 8 mg: 100 mL, and the photoinitiator was selected from photoinitiator 1173. After the reaction was completed, ethyl acetate was removed by rotary evaporation to obtain a surface modifier.
[0044] Step A2: The surface modifier and acetone are heated to 50°C for mixing, conductive carbon black is added for ultrasonic dispersion, and the dispersion is allowed to stand for 24 hours, wherein the feed ratio of conductive carbon black, surface modifier and acetone is 50g:3.8g:300mL, and the conductive carbon black is selected from LI-400 type raw material with an average particle size of 48nm. Then, the bottom precipitate is washed with ethanol, and the precipitate is centrifuged again and vacuum dried to constant weight to obtain modified carbon black.
[0045] Step A3: Stir and disperse the modified carbon black, aniline and tetrahydrofuran, then add hydrochloric acid to mix, control the temperature of the water bath to 55°C, apply 90rpm stirring and slowly add ammonium persulfate solution to react for 4.5h, wherein the feed ratio of modified carbon black, aniline, ammonium persulfate, hydrochloric acid and tetrahydrofuran is 50g:9g:1.4g:400mL:90mL, the ammonium persulfate solution is a saturated aqueous solution at room temperature, and the concentration of hydrochloric acid is 1mol / L. After the reaction is completed, centrifuge the precipitate, wash with water to neutrality, and dry to obtain high gloss carbon black.
[0046] (2) Preparation of PP composite materials
[0047] Ingredients: The raw materials are calculated by weight: 100 parts of PP resin, K1008 type resin raw material is selected; 17 parts of POE resin, LC670 type resin raw material is selected; 10 parts of high gloss carbon black, which is self-made in this embodiment; 0.7 parts of antistatic additive, selected from sodium dodecylbenzene sulfonate; 12 parts of filler, selected from talcum powder and glass fiber powder, compounded in a weight ratio of 2:1; 3.2 parts of lubricant, selected from calcium stearate; 0.15 parts of antioxidant, selected from antioxidant 1010 and antioxidant 168, compounded in a weight ratio of 1:1.
[0048] Blending: Premix high gloss carbon black, antistatic additive and filler, then melt blend PP resin, POE resin, lubricant and antioxidant at 180°C, then add the premix, continue to heat to 210°C and knead until the torque is stable, cool the material out, and obtain a PP composite material.
[0049] Example 4, preparation of an antistatic PP composite material based on high gloss carbon black, the specific implementation process is as follows:
[0050] (1) Preparation of high gloss carbon black
[0051] Step A1: Preheat pentaerythritol tetraacrylate, p-hydroxythiophenol and ethyl acetate to 40°C for mixing, introduce nitrogen for protection, then add photoinitiator and mix well, then control the temperature to 65°C, use 180W / m 2 UV irradiation was applied and stirred at 120 rpm for 2.8 hours, wherein the feed ratio of pentaerythritol tetraacrylate, p-hydroxythiophenol, photoinitiator and ethyl acetate was 10 mmol: 40 mmol: 8 mg: 100 mL, and the photoinitiator was selected from photoinitiator 1173. After the reaction, ethyl acetate was removed by rotary evaporation to obtain a surface modifier.
[0052] Step A2: The surface modifier and acetone are heated to 50°C for mixing, conductive carbon black is added for ultrasonic dispersion, and the dispersion is allowed to stand for 24 hours, wherein the feed ratio of conductive carbon black, surface modifier and acetone is 50g:4g:300mL, the conductive carbon black is selected from VULCAN XC-72 raw material, and the average particle size is 30nm. Then, the bottom precipitate is washed with ethanol, and the precipitate is centrifuged again and vacuum dried to constant weight to obtain modified carbon black.
[0053] Step A3: Stir and disperse the modified carbon black, aniline and tetrahydrofuran, then add hydrochloric acid to mix, control the temperature of the water bath to 50°C, apply 90rpm stirring and slowly add ammonium persulfate solution to react for 5 hours, wherein the feed ratio of modified carbon black, aniline, ammonium persulfate, hydrochloric acid and tetrahydrofuran is 50g:9g:1.6g:350mL:80mL, the ammonium persulfate solution is a saturated aqueous solution at room temperature, and the concentration of hydrochloric acid is 1mol / L. After the reaction is completed, centrifuge and take the precipitate, wash with water to neutrality, and dry to obtain high gloss carbon black.
[0054] (2) Preparation of PP composite materials
[0055] Ingredients: The raw materials are calculated by weight: 100 parts of PP resin, K1008 type resin raw material is selected; 18 parts of POE resin, LC670 type resin raw material is selected; 11 parts of high gloss carbon black, which is self-made in this embodiment; 0.7 parts of antistatic additive, selected from sodium dodecylbenzene sulfonate; 13 parts of filler, selected from talcum powder and glass fiber powder, compounded in a weight ratio of 2:1; 3 parts of lubricant, selected from calcium stearate; 0.15 parts of antioxidant, selected from antioxidant 1010 and antioxidant 168, compounded in a weight ratio of 1:1.
[0056] Blending: Premix high gloss carbon black, antistatic additive and filler, then melt blend PP resin, POE resin, lubricant and antioxidant at 190°C, then add the premix, continue to heat to 210°C and knead until the torque is stable, cool the material out, and obtain a PP composite material.
[0057] In Comparative Example 1, the high gloss carbon black in Example 4 was replaced with Raven 1060 Ultra commercially available high gloss carbon black, and the rest of the implementation process was exactly the same as that in Example 3.
[0058] Comparative Example 2, polyaniline-carbon black particles were prepared with reference to the prior art, and the specific method was as follows: aniline and hydrochloric acid were stirred and dispersed, conductive carbon black was added and ultrasonically dispersed for 30 minutes, and then the ammonium persulfate solution was slowly added to the dispersion, and the reaction time was controlled to be 8 hours, wherein the feed ratio of conductive carbon black, aniline, ammonium persulfate and hydrochloric acid was 50g:10g:2.2g:500mL, and the reaction was completed by centrifugation to obtain the precipitate, washed with water to neutrality, and dried to obtain polyaniline-carbon black particles; an equal amount of the precipitate was used to replace the high gloss carbon black in Example 4, and the rest of the implementation process was exactly the same.
[0059] The PP composite material obtained as above was taken, and a sheet was hot pressed at 220°C and 2.0MPa using a flat vulcanizer, and then cut and sampled. The surface resistivity was tested according to the IEC 61340 5-1-2016 standard, and the static decay time was tested according to the ANSI / ESDS20.20-2021 standard; the 60° angle gloss was tested according to the GB / T 8807-1988 standard; the specific test results are shown in Table 1:
[0060] Table 1 Test results of antistatic properties and glossiness of samples
[0061]
[0062] It can be seen from the test results in Table 1 that the embodiment has good antistatic performance compared with the comparative example, while maintaining a high gloss. Based on the above test results, the high gloss carbon black prepared in Example 4 was observed by electron microscopy. Figure 1 , high gloss carbon black is spherical and has a relatively smooth surface.
[0063] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0064] The above contents are merely examples and explanations of the concept of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. An antistatic PP composite material based on high gloss carbon black, characterized in that: The following raw materials are included by weight: 100 parts of PP resin, 15-20 parts of POE resin, 8.5-12 parts of high gloss carbon black, 0.6-0.8 parts of antistatic additive, 10-15 parts of filler, 2.5-3.5 parts of lubricant and 0.12-0.15 parts of antioxidant; Step A1: Preheat pentaerythritol tetraacrylate, p-hydroxythiophenol and ethyl acetate to dissolve, introduce nitrogen protection, then add photoinitiator and mix well, then control the temperature to 55-70°C, use 150-220W / m 2 UV irradiation, stirring and reacting for 2.5-3.5 hours, removing ethyl acetate after the reaction is completed to obtain a surface modifier; Step A2: Mix the surface modifier and acetone at a high temperature, add the conductive carbon black and disperse them by ultrasonic, then let the dispersion stand for 24 hours, take the bottom precipitate and wash it with ethanol, centrifuge it again and vacuum dry it to constant weight to obtain modified carbon black; Step A3: The modified carbon black, aniline and tetrahydrofuran are stirred and dispersed, and then hydrochloric acid is added and mixed. The temperature of the water bath is controlled at 40-60° C., and ammonium persulfate solution is slowly added to react for 3.5-5.5 hours. After the reaction is completed, the precipitate is centrifuged and washed with water until neutral and dried to obtain high gloss carbon black; The feed ratio of pentaerythritol tetraacrylate, p-hydroxythiophenol, photoinitiator and ethyl acetate is 10mmol:40mmol:6-10mg:80-110mL; The feed ratio of conductive carbon black, surface modifier and acetone is 50g:3.2-4.4g:270-350mL; The average particle size of conductive carbon black is 30-50nm; The feed ratio of modified carbon black, aniline, ammonium persulfate, hydrochloric acid and tetrahydrofuran is 50g:7.8-9.5g:1.2-1.8g:300-400mL:70-90mL.
2. The antistatic PP composite material based on high gloss carbon black according to claim 1, characterized in that: The antistatic auxiliary agent is selected from anionic antistatic agents.
3. The antistatic PP composite material based on high gloss carbon black according to claim 1, characterized in that: The filler is compounded from talcum powder and glass fiber powder.
4. A method for preparing an antistatic PP composite material based on high gloss carbon black according to any one of claims 1 to 3, characterized in that: Specifically, high gloss carbon black, antistatic additive and filler are premixed, and then PP resin, POE resin, lubricant and antioxidant are melt-blended at 180-190°C, and then the premix is added, and the temperature is continued to be raised to 210°C and kneaded until the torque is stable, and the material is cooled to obtain a PP composite material.
Citation Information
Patent Citations
High-strength conductive plastic and preparation method thereof
CN114874543A
Modified carbon black as well as preparation method and application thereof
CN117229655A